Paradigma Perdagangan Dalam Islam (Telaah Taradhin Dalam Akad Jual-Beli) - arizqiya nurfattah; Nurus Shefrilianti Hidayatullah; Afif, Mufti; Nasrudin Fajri, Mohammad Zen (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2024)
This study discusses trading from the Qur'an perspective, which focuses on tharadin related to buying and selling carried out online. Trading must be initiated by Allah to obtain profits and blessings. Thus, by shunning all its prohibitions we have become obedient and obedient servants of all its commandments and prohibitions. The purpose of this study is to provide an understanding of the concept of trading, namely ar-rida ruknu li al-akad. The research method used is a qualitative method, with a descriptive approach through library research. Tharadin in the contract of buying and selling is one of the pillars that must be fulfilled. At-tharadin is the main pillar of the validity of a sale and purchase because compulsion in transactions will cancel the sale and purchase contract and the law is invalid.